Między egzotyzmem a nowoczesnością - Jerzego Bandrowskiego spojrzenia na azjatycki świat („Tygodnik Ilustrowany” 1919) - Gabryś-Sławińska, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is to analyze Jerzy Bandrowski’s reportage, which was published on the pages of “The Illustrated Weekly” in 1919. The reportage is examined through the prism of the information strategy adopted by the weekly after Poland regained independence. Such information strategy involved searching for new forms of expression, themes and motives in the shifting political and cultural situation. The analysis reveals that the reportage, on the one hand, is a continuation of the current model of presenting Asian distinctness (exoticism), and on the other hand, it is an attempt to offer readers a new perspective on Asian culture (mainly Japanese) as something modern and familiar.